ANALISIS KINERJA KEUANGAN PADA CV ITHSAN INFOTIKA - Yunizar Herianti; Tuti Fitriani (CV. ADIBA AISHA AMIRA, 2025)
This research aims to determine financial performance in terms of activity performance and company profitability. This research is descriptive research with data collection techniques using documentation and interview techniques. The data analysis instrument used is financial ratios including total asset turnover ratio, inventory turnover, gross profit margin, operating profit margin, net profit margin, return on assets. The results of the analysis show that financial performance in terms of activity for inventory turnover ratio is classified as good, while in terms of total asset turnover ratio it is classified as poor. In terms of financial performance, profitability for less than good gross profit margin ratios is classified as good. Furthermore, the operational profit margin ratio is included in the poor category. The net profit margin ratio is included in the good category and the Return On Assets ratio is included in the good category.